1989
DOI: 10.1159/000242906
|View full text |Cite
|
Sign up to set email alerts
|

Bile Secretory Apparatus in the Newborn Dog: Relationship between Structural and Functional Immaturities

Abstract: In the dog, bile secretion is not fully mature at birth and develops during postnatal life. To try to establish morphologic correlates to the physiologic deficiencies, we examined the ultrastructure of hepatic parenchyma and biliary epithelium in a newborn puppy and in 3 puppies of 1, 3, and 7 days of age. At birth, the hepatocytes contain much glycogen and fat droplets, a small smooth endoplasmic reticulum and Golgi apparatus, rare autophagic vacuoles, and numerous lysosomes. The sinusoidal microvilli are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The data presented in this study as well as other recently published information [14,25,32,37,38] indicate that the suckling dog may be an excellent model for the study of milk fat digestion in the suckling infant. Similarities between the newborns of these two species include: similar localization and activity levels of gastric lipase in the puppy to those described recently in human infants [32], immature bile-secretory function in the newborns of both dog and human [4,37], presence of bile-salt-stimulated lipase in the milk [8, 11,25], as well as similar fatty-acid composition of milk fat [38,39].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The data presented in this study as well as other recently published information [14,25,32,37,38] indicate that the suckling dog may be an excellent model for the study of milk fat digestion in the suckling infant. Similarities between the newborns of these two species include: similar localization and activity levels of gastric lipase in the puppy to those described recently in human infants [32], immature bile-secretory function in the newborns of both dog and human [4,37], presence of bile-salt-stimulated lipase in the milk [8, 11,25], as well as similar fatty-acid composition of milk fat [38,39].…”
Section: Discussionsupporting
confidence: 74%
“…Similarities between the newborns of these two species include: similar localization and activity levels of gastric lipase in the puppy to those described recently in human infants [32], immature bile-secretory function in the newborns of both dog and human [4,37], presence of bile-salt-stimulated lipase in the milk [8, 11,25], as well as similar fatty-acid composition of milk fat [38,39].…”
Section: Discussionmentioning
confidence: 77%
“…In the dog, the structure of the liver, particularly the structure of liver cells (hepatocytes and bile ductular cells), and the biliary tree and associated passages attain adult characteristics by postnatal week 1 (Tavoloni et al, 1985; Tavoloni and Schaffner, 1989). Specifically, Tavoloni and Schaffner (1989) reported that most structural maturation occurs during the first 3 days after birth, with full maturity of the biliary tree occurring by the end of postnatal week 1.…”
Section: Accessory Organs Of Digestionmentioning
confidence: 99%
“…In pigs aged 3–6 days, the majority of bile acids that were secreted were conjugated to glycine or taurine (Henning, 1981). In dogs, bile secretory function of the liver is not fully mature at birth but was between 30 and 70% of adult values by postnatal weeks 4–6 (Tavoloni et al, 1985; Tavoloni and Schaffner, 1989). Tavoloni et al (1985) reported that in newborn dogs, canalicular bile flow was decreased compared to adults while ductular bile water reabsorption was virtually absent.…”
Section: Accessory Organs Of Digestionmentioning
confidence: 99%
See 1 more Smart Citation